Quantum Teaching Dengan Teknik Debat Dalam Upaya Stimulus Keaktifan Intelektual Siswa Pada Mata Pelajaran Fiqih - Hengki Satrisno (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Quantum Teaching with Debate Technique in an Effort to Stimulate Student Intellectual Activity in Fiqh Lesson Quantum teaching with debate technique is an implemented method aimed at stimulating students' intellectual activity. The implication shows an increase in students' intellectual activeness. As seen from the learning outcomes of students in the first cycle by 60% and the average value obtained 66, increased in the second cycle to 72%. Mastery learning students and the average value obtained 69.4, mastery learning students do not stop until the second cycle only, in the third cycle students' mastery learning becomes 88% with an average value obtained by students by 74. While the results of observation shows the activeness of students that in the first cycle the average score of student activeness was 17.5 with sufficient criteria, in cycle II there was a significant increase in student activeness by 20 with sufficient criteria, whereas in the third cycle, student activeness was seen from an increase in scores of 25.5 with good criteria.Abstrak : Quantum Teaching Dengan Teknik Debat Dalam Upaya Stimulus Keaktifan Intelektual Siswa Pada Mata Pelajaran Fiqih Quantum teaching dengan teknik debat merupakan metode yang diimplementasikan bertujuan untuk menstimulasi keaktifan intelektual siswa . Implentasinya menunjukan adanya peningkatan keaktifan intelektual siswa.yang terlihat dari hasil belajar siswa pada siklus I sebesar 60 % dan rata-rata nilai yang diperoleh 66, meningkat pada siklus II menjadi 72%. Ketuntasan belajar siswa dan nilai rata-rata yang diperoleh 69,4, ketuntasan belajar siswa tidak berhenti sampai disiklus ke II saja, pada siklus ke III ketuntasan belajar siswa menjadi 88% dengan nilai rata-rata yang diperoleh oleh siswa sebesar 74. Sedangkan hasil observasi menunjukan keaktifan siswa bahwa pada siklus I skor rata-rata keaktifan siswa sebesar 17,5 dengan kriteria cukup, pada siklus II terjadi peningkatan yang signifikan terhadap keaktifan siswa sebesar 20 dengan kriteria cukup, sedangkan pada siklus ke III, keaktifan siswa terlihat dari kenaikan skor sebesar 25,5 dengan kriteria baik